Home > Math > Detail
search_icon
Question

What is the solution to the equation 4(−5−2x)−3x=−5(2x+6)

Answer

The value of x is 10. Step-by-step explanation: 1. Begin by simplifying the equation: 4(-5-2x) - 3x - 20 - 11x = -5(2x+6). 2. Expand the brackets: -20 - 8x - 3x - 20 - 11x = -10x - 30. 3. Collect like terms: -22x - 40 = -10x - 30. 4. Add 10x to both sides: -22x - 40 + 10x = -30. 5. Simplify: -12x - 40 = -30. 6. Add 40 to both sides: -12x = 10. 7. Divide by -1: x = -10/(-1). 8. Simplify: x = 10.